Two new freshwater gobiid species of Rhinogobius Gill, 1859 (Teleostei: Gobiidae) from Taiwan - Chen, I-Shiung; Yeh, Ming-Fon (Zootaxa, 2024)
Two new freshwater gobies of Rhinogobius were discovered from Taiwan. They are fluvial species belonging to R. rubromaculatus complex. The new species, Rhinogobius baborinisanensis n. sp. which is collected from northern Taiwan can be well distinguished from all other congeners by the unique combination of the following features: (1) fins: second dorsal fin rays modally I/8; anal fin rays I/7; pectoral fin rays modally 17; (2) squamation: longitudinal scale series 32–34 (modally 33); perdorsal scales usually 13–14; scale series from origin of first dorsal fin to upper pectoral fin origin modally 10; (3) vertebral count 27; (4) rear edge of mouth merely extending to or slightly beyond vertical of anterior margin of pupil in male and (5) its own specific colouration. Another new species, Rhinogobius macromaculatus n. sp. which is collected from southern Taiwan can be well distinguished from all other congeners by the unique combination of the following features: (1) fins: second dorsal fin rays modally I/8; anal fin rays I/7; pectoral fin rays modally 15; (2) squamation: longitudinal scale series 27–28 (modally 28); perdorsal scales usually 14–15; scale series from origin of first dorsal fin to upper pectoral fin origin modally 8; (3) vertebral count 27; (4) rear edge of mouth extending slightly beyond vertical of anterior margin of pupil in male and (5) its own specific colouration. The brief comparison and discussion of morphological differentiation from congeners would be also addressed.